Giant barocaloric tunability in [(CH3CH2CH2)4N]Cd[N(CN)2]3 hybrid perovskite. Issue 37 (6th September 2018) - Bermúdez-García, Juan Manuel; Yáñez-Vilar, Susana; García-Fernández, Alberto; Sánchez-Andújar, Manuel; Castro-García, Socorro; López-Beceiro, Jorge; Artiaga, Ramón; Dilshad, Melony; Moya, Xavier; Señarís-Rodríguez, María Antonia
Abstract : [TPrA]Cd[dca]3 shows giant barocaloric tunability and large barocaloric effect, which are desirable for future low-pressure barocaloric cooling applications. Abstract : We report the barocaloric performance of cadmium-dicyanamide perovskite [(CH3 CH2 CH2 )4 N]Cd[N(CN)2 ]3 ([TPrA]Cd[dca]3 ). The introduction of Cd, a large second-row post-transition metal, into this hybrid organic–inorganic perovskite structure leads to three separate thermally driven phase transitions and four polymorphs, which we characterize in full using temperature-dependent X-ray diffraction and temperature-dependent calorimetry. Amongst these transitions, the non-isochoric orthorhombic to tetragonal phase transition at high temperatures, with a large volume change of ∼0.4%, leads to a large reversible pressure-driven isothermal change in entropy of ∼11.5 J K −1 kg −1, and a giant barocaloric tunability of the transition temperature with pressure of ∼38.2 K kbar −1, which are both desirable for future low-pressure barocaloric cooling applications.